\(x\times y-x+2\times y=1\)1
\(x\times\left(y-1\right)+2\times y-2=1-2\)
\(x\times\left(y-1\right)+2\times\left(y-1\right)=-1\)
\(\left(x+2\right)\times\left(y-1\right)=-1=1\times\left(-1\right)=\left(-1\right)\times1\)
\(\Rightarrow\hept{\begin{cases}x+2=1\\y-1=-1\end{cases}\Rightarrow\hept{\begin{cases}x=-1\\y=0\end{cases}}}\)
\(\Rightarrow\hept{\begin{cases}x+2=-1\\y-1=1\end{cases}\Rightarrow\hept{\begin{cases}x=-3\\y=2\end{cases}}}\)
Vây...
xy-x+2y=1
x(y-1)+2y=1
x(y-1)+2y-2=1-2
x(y-1)+2(y-1)=-1
(x+2)(y-1)=-1
<=>-1⋮y-1
<=>y-1∈Ư(-1)={-1;1}
<=>y∈{0;2}
Nếu y=0 thì xy-x+2y = x.0-x+2.0=1
0-x+0=1
-x=1
x=-1
Nếu y=1 thì xy-x+2y = x.1-x+2.1=1
x-x+2=1
2=1(vô lí ***)
Vậy x=-1;y=0
2 = hi
vừa nãy bị lộn
Nếu y=2 chứ ko phải là y=1
Nếu y=2 thì x.2-x+2.2=1
x+4=1
x=1-4
x=-3
Vậy nếu x=-1 thì y=0; x=-3 thì y=2